2009
DOI: 10.1088/0953-4075/42/19/195202
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of power broadening in strong-coupling photoassociation in the presence of a Feshbach resonance

Abstract: Abstract.Photoassociation (PA) spectrum in the presence of a magnetic Feshbach resonance is analyzed. Nonperturbative solution of the problem yields analytical expressions for PA linewidth and shift which are applicable for arbitrary PA laser intensity and magnetic field tuning of Feshbach Resonance. We show that by tuning magnetic field close to Fano minimum, it is possible to suppress power broadening at increased laser intensities. This occurs due to quantum interference of PA transitions from unperturbed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Over the last 4 years, several such experiments [42][43][44][45][46] have been carried out. The results of these experiments as well as theoretical studies [47][48][49][50][51][52][53] PA spectrum is usually determined by measuring the loss of atoms from atomic traps due to a PA laser. Once a bound state is formed in an excited molecular potential by PA process, this bound state can spontaneously decay to either two hot atoms or a bound state in ground molecular potential close to dissociation threshold.…”
Section: Nancementioning
confidence: 99%
“…Over the last 4 years, several such experiments [42][43][44][45][46] have been carried out. The results of these experiments as well as theoretical studies [47][48][49][50][51][52][53] PA spectrum is usually determined by measuring the loss of atoms from atomic traps due to a PA laser. Once a bound state is formed in an excited molecular potential by PA process, this bound state can spontaneously decay to either two hot atoms or a bound state in ground molecular potential close to dissociation threshold.…”
Section: Nancementioning
confidence: 99%
“…However, here we show that, by establishing a coherence between two excited ro-vibrational levels by two lasers, it is possible to suppress this inelastic loss significantly. Previous studies [22][23][24] on Fano-Feshbach resonances in PA [22] in the presence of a MFR [25][26][27] primarily focused on controlling s-wave scattering states, suppression of inelastic scattering [23], and control over power broadening [24]. The present work is basically concerned with optical manipulation of the anisotropic atom-atom interaction.…”
Section: Introductionmentioning
confidence: 98%
“…OFR has been demonstrated in recent experiments [17,18,19]. Recently, PA spectroscopy in the presence of an MFR has attracted a lot of attention both experimentally [20,21,22,23] and theoretically [24,25,26,27,28]. Junker et al [20] have observed asymmetric profile in PA spectrum under the influence of an MFR.…”
Section: Introductionmentioning
confidence: 99%